Using Financial Analysis Methods in the Hotel Sector for the Purposes of Planning and Monitoring Case Study Al Zaitonia Hotel - Jawabreh, Omar A.A.; Mahmoud, Rami Muneer; Al Momani, Emran (International Journal of Economics and Financial Issues, 2017)
The study aimed at indicating the most important factors that control the takings and expenses of the hotel and classifying them according to their ability to influence the profitability of the hotel by using the appropriate analytical financial methods for the hotel activity which contribute in increasing the efficiency of planning and monitoring the hotel activity. The study indicated that the average spending power of the single guest and the numbers of guests are the basic factors that form the hotel's revenues, where the spending power of the single guest was the most powerful factor to influence the profitability of the hotel activity. Accommodation represents the most important factor in forming the spending power for the single guest and consequently influences profitability. The study also showed that the changing and fixed costs elements directly affect profitability and control the activity of the hotel sector and they, therefore, need planning, monitoring and following up by those in charge. Keywords: Financial Analysis, Hotel, Development Planning, Financial services financial management. JEL Classifications: G00, L83,O20, G200, M400.